Comparison of Physical Ability Based on Player Position: Study on Volleyball Club VOPAS Semarang Year 2025 - Priambodo, Erwin Nizar; Nasuka, Nasuka; Yudhistira, Dewangga; Dameria, Franciska Dina (Universitas Majalengka, 2025)
Background: Physical performance analysis in the VOPAS Semarang volleyball club has not received special attention because it is constrained by aspects of understanding and field practice. Purpose: to analyze physical abilities based on the position of libero, setter, and spike players punched from flexibility, speed, strength and jump height. Methods: Descriptive quantitative comparative as research method. Participants were volleyball players of club VOPAS Semarang, 34 males, aged 15-19 years. Data collection techniques with tests. The instruments were sit and reach, 10-20 meter sprint, hand grip and vertical jump. Data analysis techniques descriptive and kruskall wallis test assisted with SPSS version 23. Results: Flexibility aspect is 100% excellent category, 21% jump height is poor, 70% strength is very poor, 20 meter sprint is 100% very poor, 10 meter sprint is 41% average, kruskall wallis test overall aspects get a significance value of (p>0.05). Conclusion: Improvement is needed in the aspects of speed and strength, physical aspects in terms of player position did not have significant differences. This information can be a reference for further research and useful for the VOPAS volleyball club in physical development. Research limitations need to be improved in a wider sample, and other physical aspects must be added to make it more comprehensive.